Circulating growth/differentiation factor 15 is associated with human CD56bright natural killer cell dysfunction and nosocomial infection in severe systemic inflammationResearch in context - Holger Kleinertz; Monika Hepner-Schefczyk; Sabrina Ehnert; Maren Claus; Rebecca Halbgebauer; Lea Boller; Markus Huber-Lang; Paolo Cinelli; Carsten Kirschning; Sascha Flohé; André Sander; Christian Waydhas; et al. (EBioMedicine, 2019)
Background: Systemic inflammation induced by sterile or infectious insults is associated with an enhanced susceptibility to life-threatening opportunistic, mostly bacterial, infections due to unknown pathogenesis. Natural killer (NK) cells contribute to the defence against bacterial infections through the release of Interferon (IFN) γ in response to Interleukin (IL) 12. Considering the relevance of NK cells in the immune defence we investigated whether the function of NK cells is disturbed in patients suffering from serious systemic inflammation. Methods: NK cells from severely injured patients were analysed from the first day after the initial inflammatory insult until the day of discharge in terms of IL-12 receptor signalling and IFN-γ synthesis. Findings: During systemic inflammation, the expression of the IL-12 receptor β2 chain, phosphorylation of signal transducer and activation 4, and IFN-γ production on/in NK cells was impaired upon exposure to Staphylococcus aureus. The profound suppression of NK cells developed within 24 h after the initial insult and persisted for several weeks. NK cells displayed signs of exhaustion. Extrinsic changes were mediated by the early and long-lasting presence of growth/differentiation factor (GDF) 15 in the circulation that signalled through the transforming growth factor β receptor I and activated Smad1/5. Moreover, the concentration of GDF-15 in the serum inversely correlated with the IL-12 receptor β2 expression on NK cells and was enhanced in patients who later acquired septic complications. Interpretation: GDF-15 is associated with the development of NK cell dysfunction during systemic inflammation and might represent a novel target to prevent nosocomial infections. Fund: The study was supported by the Department of Orthopaedics and Trauma Surgery, University Hospital Essen. Keywords: Natural killer cells, Opportunistic infections, Interferon gamma, Interleukin 12, Transforming growth factor receptor, Immunosuppression